Colossal 3D Electrical Anisotropy of MoAlB Single Crystal. Issue 5 (27th November 2021) - Huang, Yanan; Si, Jianguo; Lin, Shuai; Lv, Hongyan; Song, Wenhai; Zhang, Ranran; Luo, Xuan; Lu, Wenjian; Zhu, Xuebin; Sun, Yuping
Abstract: 3D anisotropic functional properties (such as magnetic, electrical, thermal, and optical properties, etc.) in a single material are not only beneficial to the multipurpose of a material, but also helpful to enrich the regulatory dimensionality of functional materials. Herein, a colossal 3D electrical anisotropy of layered MAB‐phase MoAlB single crystal is introduced and dissected. Using high‐temperature metal‐solution method, high‐quality MoAlB single crystals are obtained and a surprisingly strong out‐of‐plane ( σa / σb = 1.43 × 10 5, at 2 K) and in‐plane ( σa / σc = 12.12, at 2 K) electrical anisotropies are first observed. After a series of experimental and theoretical investigations, it is demonstrated that the 3D anisotropic crystal structure and chemical bond of MoAlB result in its 3D anisotropic phonon vibration and electronic structure, influence the corresponding electron‐electron as well as electron‐phonon interactions, and finally give rise to its colossal 3D anisotropy of electrical conductivity. This work experimentally and theoretically proves MoAlB single crystal possessing the 3D anisotropies of crystal structure, chemical bond, phonon vibration, electronic structure, and electrical transport, but also provides a promising platform for the future design of functionalized electronic devices as well as synthesis of new and large‐sized in‐plane anisotropic 2D material (MoBene). Abstract : A colossal 3D anisotropy of electrical conductivity is firstly observed in layered MAB‐phase MoAlB single crystal. The origin is dissected from experimental and theoretical insights. The 3D anisotropic crystal structure and chemical bond of MoAlB result in its 3D anisotropic phonon vibration as well as electronic structure, and finally give rise to its colossal 3D anisotropy of electrical conductivity.